2020
DOI: 10.1088/1757-899x/773/1/012027
|View full text |Cite
|
Sign up to set email alerts
|

UV-protection property of Eri silk fabric dyed with natural dyes for eco-friendly textiles

Abstract: Eri silk (Samia ricini) is a wild silkmoth which has been promoted and supported to culture for textile industry in Thailand. Especially for the recent decade, textile industry was interested to develop eri silk for casual eco-friendly textile style with functional properties. This research aims to study on UV protection property of eri silk fabric dyed with natural dyes from plant extracts and their washing fastness property. The processes included extracting the colorants from Thai plants i.e. natural indigo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…This would help make good use of fruit waste while simultaneously shielding the skin from harmful UV radiation. Rungruangkitkrai et al (2020) In the present work, Salah et al ( 2013) investigated the alkaline peel fractions as a UV protective agent, dye, and multifunctional antibacterial on the cotton substrate. The results collected demonstrated that mercerized textiles exhibited superior UV protection, high dye absorption, and outstanding antibacterial activity when compared to control and unmercerized cotton fabrics.…”
Section: Ultraviolet C Radiationmentioning
confidence: 94%
“…This would help make good use of fruit waste while simultaneously shielding the skin from harmful UV radiation. Rungruangkitkrai et al (2020) In the present work, Salah et al ( 2013) investigated the alkaline peel fractions as a UV protective agent, dye, and multifunctional antibacterial on the cotton substrate. The results collected demonstrated that mercerized textiles exhibited superior UV protection, high dye absorption, and outstanding antibacterial activity when compared to control and unmercerized cotton fabrics.…”
Section: Ultraviolet C Radiationmentioning
confidence: 94%
“…There is an increasing demand for the pursuit of efficient novel UV irradiance-blocking materials as a result of sustained exposure for the harmful UV radiation all over the globe and the limitations of the traditional UV absorbers [1][2][3]. UV radiation exposure can cause serious health problems for humans, such as cancers, sunburns, eye, and DNA damage [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, perovskites recorded high degradation impact associated with UV absorption [8][9][10]. Consequently, scholars were motivated to fabricate facile, cost-effective, green, and sustainable UV protection layers for industrial purposes [3,11,12].…”
Section: Introductionmentioning
confidence: 99%